Staurosirella paranaensis sp. nov., a new epiphytic freshwater diatom (Bacillariophyceae) from the Paraná River floodplain, Brazil, South America - Osório, Nicolli C.; Ector, Luc; Rodrigues, Liliana; Wetzel, Carlos E. (Phytotaxa, 2021)
A new diatom species, Staurosirella paranaensis, is described only from epiphytic samples on the macrophyte Eichhornia azurea in a lake from the Upper Paraná River Floodplain in Brazil. Description of the new taxon is based on morphological characteristics observed using light and scanning electron microscopy. The new species is characterized by short elliptic valves with an axial area narrowly lanceolate, sometimes giving the impression of having a zig-zag form due the alternating nature of the striae. The lineolate striae, running uninterrupted from valve face to mantle. Spines are solid, thin, spatulate with two prominences at the top, located at the costae. Apical pore fields are inconspicuous, located at both apices and equally developed on both valves. Girdle elements variable in number, open, lacking pores, ligulated, and with valvocopula being much larger. The species previously identified in the region as the “catch-all” taxon “Staurosirella (Staurosira) pinnata” is placed in the genus Staurosirella based on the striae bearing well-developed internal vimines delimiting typically long areolae. Comparisons with similar species ascribed to the genus Staurosirella are provided to highlight the peculiar characteristics of S. paranaensis.